2010
DOI: 10.1002/jssc.200900697
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid quantitation in hand dishwashing liquid using an HILIC‐UV methodology

Abstract: Different hydrophilic interaction chromatography (HILIC) columns were screened for lactic acid separation in hand dishwashing liquid products and the influence of mobile phase strength, buffer concentration and column temperature on the retention of lactic acid on a Zorbax NH(2) column was investigated. An isocratic HILIC method for the quantitation of lactic acid in hand dishwashing liquid products was developed. The mobile phase consists of 70% methanol and 30% 20 mM sodium phosphate buffer (v/v) at pH 2.5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…An elevated temperature could also decrease retention time. When a temperature increase makes analyte retain longer on a column, the retention difference between individual analytes can be enlarged, resulting in improved resolution [19, 47]. In this study, a longer arginine retention time was observed at a higher column temperature.…”
Section: Resultsmentioning
confidence: 59%
“…An elevated temperature could also decrease retention time. When a temperature increase makes analyte retain longer on a column, the retention difference between individual analytes can be enlarged, resulting in improved resolution [19, 47]. In this study, a longer arginine retention time was observed at a higher column temperature.…”
Section: Resultsmentioning
confidence: 59%
“…On the basis of our experience from the HILIC studies and the literature review, , HILIC methods were explored for CBD quantification in hemp seed oil samples. The HILIC retaining power is mainly provided by hydrophilic partitioning, hydrogen bonding, electrostatic, and adsorptive interactions, which are different from those of RP-HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…As the pH of the mobile phase is increased over the acidic range, surface silanols become negatively charged resulting in increased polarity of the stationary phase. Increase in molar strength of the mobile phase results in increased retention of acidic compounds . Since the mechanism of the HILIC mode is orthogonal to reversed‐phase LC, the order of elution of the chromatograms of the target compounds on the C18 column (Fig.…”
Section: Resultsmentioning
confidence: 99%